An Analysis on Local Convergence of Inexact Newton-Gauss Method for Solving Singular Systems of Equations - Fangqin Zhou (The Scientific World Journal)
We study the local convergence properties of inexact Newton-Gauss method for singular systems of equations. Unified estimates of radius of convergence balls for one kind of singular systems of equations with constant rank derivatives are obtained. Application to the Smale point estimate theory is provided and some important known results are extended and/or improved.